CALCULATION METHODS OF ORIENTATION ANGLES OF TRANSMITTER AND NOISE RECEIVER ANTENNAS IN ANALYSIS OF ELECTROMAGNETIC COMPATIBILITY - O. I. Korolkova; V. M. Kozel; K. L. Gorbachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The calculation methods of orientation angles of transmitter and noise receiver antennas, and also calculation of the true incremental angle are explained. Dependence of an computation error of the incremental angle values is received, when using the approximate calculation formula .